Tinjauan Perencanaan Terowongan Pengelak Bendungan Karalloe di Kabupaten Gowa - Selyn Angelyca Simatupang; Benyamin Tanan; Melly Lukman (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study aims to review the planning and design of the Diversion Tunnel at the Karalloe Dam. Calculation of design rainfall analysis uses three methods namely the Gumbel Method, the Pearson Type III Log Method, and the Normal Log. The flood discharge was analyzed by the Nakayasu Synthesis Unit Hydrograph Method. Planning the Karalloe Dam Circular Tunnel is designed using a horseshoe shape, with a tunnel length of 583 m, tunnel diameter of 6 m with a height of energy loss in the tunnel of 27 m. The results showed that flood tracking with a 25 year return flood of 492,333 m / sec using a circular tunnel design obtained a tunnel diameter of 6.25 m, with a height of energy loss of 25.741 m, and a planned height of the cofferdam lighthouse +205,241 m